Numerical optimization of a RIXS spectrometer using raytracing simulations. (August 2016) - Lieutenant, K; Hofmann, T; Zendler, C; Schulz, C; Aziz, E F; Habicht, K
Abstract: At Helmholtz-Zentrum Berlin (HZB) the end-station PEAXIS (Photo Electron Analysis and X-ray resonant Inelastic Spectroscopy) combining Angle-dependent X-ray Photoelectron Spectroscopy (AdXPS) and Resonant Inelastic X-ray Scattering (RIXS) is currently built. The latter method uses a spherical variable line space (VLS) grating to focus the beam onto the detector. Working in first-order diffraction allows resolving photon energy by transferring the energy-dependent signal to a position-dependent focal spot on the detector. Focusing requires a precise combination of various parameters of the VLS grating and the geometry of the RIXS spectrometer. The VLS grating was optimized by calculating the geometry parameters for different photon energies, simulating the instrument and evaluating the pattern on the detector. As figure of merit we chose the intensity times the square of the resolving power averaged over the photon energies.